Sperm Ribosomal DNA Promoter Methylation Levels Are Correlated With Paternal Aging and May Relate With in vitro Fertilization Outcomes - Li, Lejun; Li, Hongping; Tian, Yonghong; Hu, Minhao; Le, Fang; Wang, Liya; Liu, Xiaozhen; Jin, Fan (Frontiers in Genetics, 2020)
The impact of aging on reproductive outcomes has received considerable critical attention; however, there is much less information available on the effects of paternal age compared to the effects of maternal age. In this study, methylation levels of sperm rDNA promoter regions and Long Interspersed Nucleotide Element 1 (LINE-1) were measured using pyrosequencing and fertilization, day 3 good-quality embryo, pregnancies, and implantation results were assessed. We observed significantly increasing levels of DNA methylation in the sperm rDNA promoter regions with age based on stratifying the samples by age alone (P=0.0001) and performing linear regression analysis (P<0.0001). Meanwhile, no statistically significant correlations were observed between global LINE-1 methylation with age. No statistically significant correlations were observed between sperm rDNA promoter methylation levels and either the day 3 good-quality embryo rate or clinical pregnancy rate. In contrast, the correlation between sperm rDNA promoter methylation levels and fertilization (2 pronuclei) rate was nearly significant (P=0.0707), especially the methylation levels of some individual CpG units (CpG_10, P=0.0176; CpG_11, P=0.0438; CpG_14, P=0.0232) and rDNA promoter methylation levels measured using primerS2 (P=0.0513). No significant correlation was found between sperm rDNA promoter methylation levels and fertilization rates (2 pronuclei, 1 pronuclei, and 1 polypronuclei). Our results demonstrate that sperm are susceptible to age-associated alterations in methylation levels of rDNA promoter regions, suggesting that sperm rDNA promoter methylation levels can be applied to DNA methylation-based age prediction, and that the aberrant methylation of rDNA promoters may be partially responsible for enhanced disease susceptibility of offspring sired by older fathers. Methylation levels of sperm rDNA promoter regions may correlate with polypronuclei rates of IVF programs.